2021
DOI: 10.1007/s10815-021-02137-w
|View full text |Cite
|
Sign up to set email alerts
|

Trophectoderm biopsy protocols may impact the rate of mosaic blastocysts in cycles with pre-implantation genetic testing for aneuploidy

Abstract: Purpose This study aimed to analyze the impact of different biopsy protocols on the rate of mosaic blastocysts. Methods This is a retrospective cohort study which included 115 cycles with pre-implantation genetic testing for aneuploidy (PGT-A). Two groups were allocated based on the biopsy protocols: method 1 group, the zona pellucida (ZP) was drilled on day 3 embryos followed by trophectoderm (TE) biopsy; and method 2 group, the ZP was opened on day 5 or 6 blastocysts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 35 publications
1
20
1
Order By: Relevance
“…Therefore, the no-results rate of Strategy B is higher. Contrary to Shun Xiong et al (26), our results showed that Strategy A had a lower rate of mosaic blastocyst. Mosaic embryos with mosaicism <50% transplantation could lead to a healthy pregnancy, it may be related to reduced implantation rate, increased miscarriage rate, and increased risk of fetal 229 abnormalities (27,28).…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, the no-results rate of Strategy B is higher. Contrary to Shun Xiong et al (26), our results showed that Strategy A had a lower rate of mosaic blastocyst. Mosaic embryos with mosaicism <50% transplantation could lead to a healthy pregnancy, it may be related to reduced implantation rate, increased miscarriage rate, and increased risk of fetal 229 abnormalities (27,28).…”
Section: Discussioncontrasting
confidence: 99%
“…Illumina twelve with MiSeq [ 11 , 13 , 14 , 16 , 24 , 27 , 29 , 33 , 34 , 38 , 43 , 44 ]; three with HiSeq [ 15 , 28 , 32 ]; two with NextSeq [ 31 , 41 ]; one with sequencing-by-synthesis [ 45 ]; …”
Section: Resultsmentioning
confidence: 99%
“…3). This issue may be amplified by the challenges associated with genetic analysis of very few cells, biopsy procedures potentially introducing both intact cells and fragmented cellular material (artifacts) (49,50), or incomplete lysis of cells before amplification, all of which may affect the level of noise observed. Some groups (51) have begun to address the ability to distinguish signal from noise by establishing more rigorous quality control thresholds from parameters such as the median absolute pairwise difference .…”
Section: Origins Of False Positive Mosaicismmentioning
confidence: 99%